2008
DOI: 10.1002/chem.200701562
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoly Acid Encapsulated SBA‐15/TiO2 Nanocomposites and Their Unusual Performance in Acid‐Catalysed Organic Transformations

Abstract: The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungstophosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 71 publications
(69 reference statements)
0
29
0
Order By: Relevance
“…[ 16] However, to get a clear insight into the relation between the textural parameters and the acidity of the catalysts with their performances, some of the results are presented. Low-angle XRD patterns of xT-22.4TO-S-15 with different TPA loadings and calcined at 1123 K reveal that the meso-structure of the materials is intact up to 50 wt % of TPA loading whereas the wide-angle XRD patterns of the samples show that the pure anatase phase of TiO 2 which is critical for the performing organic transformation is changed to rutile phase when the loading of TiO 2 is increased to more than 15 wt % ( Figure S1-see the supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 16] However, to get a clear insight into the relation between the textural parameters and the acidity of the catalysts with their performances, some of the results are presented. Low-angle XRD patterns of xT-22.4TO-S-15 with different TPA loadings and calcined at 1123 K reveal that the meso-structure of the materials is intact up to 50 wt % of TPA loading whereas the wide-angle XRD patterns of the samples show that the pure anatase phase of TiO 2 which is critical for the performing organic transformation is changed to rutile phase when the loading of TiO 2 is increased to more than 15 wt % ( Figure S1-see the supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…[15] As SBA-15 has interesting structural features, we have previously employed this as a support to prepare nanosized titania supported TPA composite catalysts. [16] It has been demonstrated that the SBA-15 has been a good support and the acidity of the catalysts can be tuned by the simple adjustment of the calcination temperature and the loading of the TPA in the mesochannels of the SBA-15. These nanocomposites were later tried for various organic transformations including Mannich, hydroamination (HA), and Claisen rearrangement reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its structural features, TPA has been frequently used as an efficient catalyst for various organic reactions [2][3][4][5][6]. However, TPA has such deficiencies, as extremely low surface area (< 10 m 2 g −1 ), porous structure and thermal stability, which result in the limited usage of it in various acid catalyzed reactions [7]. Therefore, it is being used after impregnation onto various carriers, such as silica, active carbon, molecular sieves, Al 2 O 3 and so on [1].…”
Section: Introductionmentioning
confidence: 99%